(3QSGdI aj JbdjO GdejJs - (3ejQRG CHh GdbGSe cdGfJQs
(3ChdgG (B:s
(3gOGjI GNJda GdCUMGH MjK bGd LhGR JbdjO GdejJ GLeGY ai YUQfG s
(3BNQgG (B:s
(3hEPG jYJHQ GdQLhY Edi GdCYde adGRe gh GdQLhY Edi ef gh CYde s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(130) s
Keywords: (3GdadSaI hGdefWbs